Irritable bowel syndrome and migraine: evidence from Mendelian randomization analysis in the UK Biobank. (3rd October 2021) - Chen, Jie; Chen, Xuejie; Xie, Ying; Sun, Yuhao; Wang, Xiaoyan; Hesketh, Therese
ABSTRACT: Background: Irritable Bowel Syndrome (IBS) and Migraine are two diseases featuring high prevalence. Previous studies have suggested a relationship between IBS and migraine, although the causal association remains unclear. The authors sought to explore the causal association between IBS and migraine, and to show the importance of migraine prevention in IBS patients. Methods: This study conducted a Mendelian randomization analysis to explore the association of IBS with migraine. Genetic association with migraine was acquired from the UK Biobank (UKB) genetic databases (cases: 1, 072; controls: 360, 122). The authors performed estimation using Inverse Variance Weighting (IVW), along with Maximum Likelihood, MR-RAPS, MR-Egger, and Weighted Median for sensitivity analysis. Considering possible bias, they also conducted polymorphism, heterogeneity, and directional analysis. Results: The IVW estimation genetically predicted the causal association between IBS and migraine (OR = 1.09, 95% CI 1.01 to 1.17, p = 0.03). Neither statistical horizontal pleiotropy (MR Egger p = 0.42; MR-PRESSO p = 0.78) nor possible heterogeneity (IVW Q = 26.15, p = 0.80) was found. Reverse causation was also not detected ( p steiger<0.01). Conclusion: Mendelian randomization analysis supported a potential causal association between IBS and migraine, providing enlightenment for disease prevention and control.